Transformasi Bisnis Berkelanjutan Melalui Model Sustainability-Led Innovation (SLI): Pendekatan Strategis Dalam Keunggulan Kompetitif - Puspitasari, Ranny Fitria; Damayanti, Vidya; Rahayu, Wening Patmi; Winarno, Agung (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
Sustainable business transformation has become a cornerstone of modern corporate strategy in addressing environmental, social, and economic challenges. The Sustainability-Led Innovation (SLI) approach provides an innovation framework that embeds sustainability principles into business models, fostering organizational adaptability and long-term value creation. This study aims to (1) identify the mechanisms for integrating SLI into sustainable business models, (2) evaluate SLI’s contribution to competitive advantage, and (3) analyze the development of dynamic capabilities to support sustainability initiatives. By combining the Sustainability-Driven Business Model Innovation (SBMI), Dynamic Capability Theory (DCT), and Triple Bottom Line (TBL) frameworks, this qualitative research utilizes in-depth interviews and document analysis of culinary SMEs in Malang. Findings reveal that organizations adopting SLI achieve higher operational efficiency, respond more agilely to regulatory changes, and attract stronger consumer loyalty. These insights underscore the necessity of embedding sustainable innovation strategies into long-term business planning to secure resilient competitive advantage.